KINERJA CAMPURAN SMA DENGAN MENGGUNAKAN PASIR PANTAI INDRAYANTI SEBAGAI PENGGANTI AGREGAT HALUS - Farkhan Ramadhan; Miftahul Fauziah (TEKNISIA, 2020)
Split Mastic Asphalt (SMA) mixture is one of the popular material for flexible pavement in Indonesia. Due to limitation of fine aggregate product  from stone crusher therefore  an alternative  sand beaches is used. This paper presents results of determine the influence of the use of coastal sand as fine aggregate subtitution on the Split mastic asphalt (SMA). This research have four phases, first testing of aggregate and asphalt properties then Determinition of optimum asphalt content 0%, 25%, 50%, 75%, and 100%. Next step were testing Marshall, Immersion, Indirect Tensile Strength, and Cantabro loss. The results showed that the use of Indrayanti's sand beach as substituted fine aggregate on the Split Mastic Ashpalt 0/11 mixture meet the standard. Based on Marshall's test stability and flexibility  of all the mixture were higher the Bina Marga  specification. Indirect Tensile Strength increase in each addition of  Indrayanti's sand beach. Cantabro Loss and Index Retained Strength on all specimens of Indrayanti's sand beach qualify Bina Marga standard.